Development of Christian Education in a Multicultural Environment - Simanjuntak, Joksan; Andrian, Tony; Saerang, Lodewyik; Rajagukguk, Wilson; Pentury, Thomas (International Journal Labs, 2025)
Christian education in a multicultural environment is crucial to develop amidst Indonesia's complex diversity. While existing studies have explored its implementation, teacher roles, and curriculum integration, a comprehensive framework for its strategic development as a proactive reform movement remains underexplored. This study aims to analyze the historical and contemporary development of Christian education in multicultural settings, identify current challenges and opportunities, and formulate strategic principles for its effective and transformative advancement. Using a qualitative descriptive method with a literature study approach, this research draws on James A. Banks' multicultural education theory and examines relevant historical, theological, and contextual sources. The findings highlight that Christian education must evolve beyond adaptation to actively shape inclusive, values-oriented, and hopeful learning environments. Strategic principles proposed include orienting education toward love and appreciation of diversity, fostering non-violent character formation, and promoting faithful engagement with pluralism. This study contributes practical guidance for educators and policymakers, enriches academic discourse on multicultural religious education, and supports the development of Christian education as a force for social harmony and unity in diversity.